Design and Fabrication of a Brace Joint With a New Mechanism for Correcting Intermittent Knee Varus and Examining Its Effect on the Gait Parameters of a Patient With Osteoarthritis of the Internal Compartment of the Knee: A Case Report - Roshanak Baghaei Roudsari; Ali Estaki; Gholamreza Aminian; Esmail Ebrahimi Takamjani; Mohammad Ebrahim Mousavi; Samaneh Hosseinzadeh (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective Knee osteoarthritis is a common, progressive, and chronic disease that affects approximately 13% of the population over the age of 60. Osteoarthritis causes progressive disability and changes in gait parameters, decreased function and quality of life of patients by causing malalignment of the knee in the frontal plane following destruction of articular cartilage. Braces as a mechanical intervention are a successful treatment for osteoarthritis knee and its associated malalignment. Using a three-point pressure mechanism, braces create a natural alignment in the knee by straps attached to the thigh and shank shells, which reduce the medial knee load and correct the varus alignment. This distributes the force properly while walking. However, applying a constant force on three pressure points of the leg, thigh and affected knee joint reduces the adduction angle of the knee in all phases of gait cycle , while the correction of the adduction angle of the knee in patients is essential only in phases between 30% to 60% of the stance phase, when the knee deviation reaches its peak. The aim of this study is to design and fabricate a brace joint with a new intermittent correction mechanism for patients with osteoarthritis medial compartment knee and to investigate its effect on a patient's gait parameters. Materials & Methods The new joint design of the knee brace was based on the conversion of the knee extension movement at the end of the swing on the sagittal plane to the abduction movement on the frontal plate by stretching the converter piece. Participant gait was assessed in two ways with and without braces. Kinematic variables including knee joint angles in the sagittal and frontal planes and spatio-temporal variables of patient gait were measured and recorded. Results The results of the new brace joint function on the knee showed that the angle of flexion of the knee in the swing phase increased from 44.72° to 46.19° when using brace. Also, knee adduction angle in the stance phase decreased from 4.25° to 2.3° and patient's walking speed while wearing the brace increased from 0.88 m/s to 0.93 m/s. On the other hand, step length increased from 1.125 m to 1.451 m when using brace and the percentage of stance phase decreased from 63.53 to 62.68 when using brace. Conclusion In this one-sample study, a knee brace with a new joint was able to help correct the direction of knee joint in the frontal and sagittal plane and affect the patient's gait parameters. It seems that if the same results are obtained in a large-scale clinical study, this brace could be a suitable replacement for invasive methods and inappropriate orthoses.